The Construction and Initial Application of Chinese College Students’ Epistemological Beliefs Questionnaire - Zhou, Yan; Tan, Dingliang (Frontiers in Psychology, 2020)
The authors construct Chinese college students’ epistemological beliefs questionnaire, which consists of six dimensions: certain knowledge, simple knowledge, acquisition of knowledge, ability to learn, speed of learning and the value of learning. The questionnaire has good reliability and validity. Using this questionnaire, based on the investigation of 1121 college students from eight different universities in China, this study aims to explore the developmental characteristics of Chinese students' epistemological beliefs. Results show that the development of college students’ epistemological beliefs follows an increased pattern; the scores of the junior and senior students are higher than the freshman and sophomore, and the scores of the sophomore are the lowest in these four groups. College students’ development on the dimensions of knowledge beliefs is higher than that of learning beliefs. The investigation and interview suggest that Chinese college students’ epistemological beliefs experience three stages: the first stage is multiplicity, the second stage is primary relativism and the third stage is advanced relativism.